Significant temperature tunability of the band gap in two-dimensional materials - Yihang Zhao; Yunxiu Li; Jinyang Xi; Jiong Yang (Computational Materials Today)
Two-dimensional (2D) materials have great attentions due to their novel physical and chemical properties. The band gap Eg plays a significant role in influencing their applications, which can be changed by the temperature. In this work, taking the Group-IV materials (graphene, silicene, germanene, and stanene) as the examples, we first study the temperature-dependent Eg by employing the state-of-the-art electron-phonon renormalization calculations. It shows that the primary Eg at K-point is almost unchanged while that at Γ-point decreases directly with temperature increase in all the systems (e.g., Eg reduction in stanene from 100 K to 500 K is 0.006 eV at K-point and 0.148 eV at Γ-point, respectively). The differences are originated from the different chemical bond characteristics at band edges, which are π-bonding at K-point but (σ*) σ (anti-) bonding at Γ-point. The latter are more sensitive to the temperature-induced vibrations, such as the out-of-plane acoustic phonon modes in the three buckling systems. The strong sensitivity of σ-bonding to the vibrations can be further examplified by another four 2D systems (P4, InSb, MgCl2, and C2F2), screening from the database MatHub-2d. This phenomenon offers the temperature tunability for the band gaps at Γ-point of 2D materials, which may have more application significances in optoelectronics.